Odor-Induced Multi-Level Inhibitory Maps in Drosophila. - Grabe, V.; Schubert, M.; Strube-Bloss, M.; Reinert, A.; Trautheim, S.; Lavista-Llanos, S.; Fiala, A.; Hansson, B.S.; Sachse, S. (eNeuro, 2020)
Optical imaging of intracellular Ca2+ influx as a correlate of neuronal excitation represents a standard technique for visualizing spatiotemporal activity of neuronal networks. However, the information-processing properties of single neurons and neuronal circuits likewise involve inhibition of neuronal membrane potential. Here, we report spatially resolved optical imaging of odor-evoked inhibitory patterns in the olfactory circuitry of Drosophila using a genetically encoded fluorescent Cl- sensor. In combination with the excitatory component reflected by intracellular Ca2+ dynamics, we present a comprehensive functional map of both odor-evoked neuronal activation and inhibition at different levels of olfactory processing. We demonstrate that odor-evoked inhibition carried by Cl- influx is present both in sensory neurons and second-order projection neurons (PNs), and is characterized by stereotypic, odor-specific patterns. Cl--mediated inhibition features distinct dynamics in different neuronal populations. Our data support a dual role of inhibitory neurons in the olfactory system: global gain control across the neuronal circuitry and glomerulus-specific inhibition to enhance neuronal information processing.